KEPUTUSAN PEMBELIAN DITINJAU KUALITAS PRODUK, LABEL HALAL DAN BRAND IMAGE - Fajritami, Khayrina Nurul; Utomo, Hastho Joko Nur (Jurnal Paradigma, 2021)
Samyang instant noodles were once a highly sought after product and had reaped the pros and cons of being halal in Indonesia. This study is to analyze the effect of product quality and halal label on purchasing decisions through brand image variables. Students majoring in Business Administration who have consumed Samyang instant noodles are the population of this study. The research sample consisted of 67 respondents, collecting data using a questionnaire. Data analysis with descriptive statistical analysis and inferential statistics (in this case Structural Equation Modeling using Smart PLS 3.0). The results of the study state that the halal label has a significant effect on brand image, has no significant effect on purchasing decisions, while product quality has a significant effect on brand image, has a significant effect on purchasing decisions and brand image has a significant effect on purchasing decisions. This study provides managerial implications in the form of the need for an integrated product planning policy that includes product quality, brand image and halal labeling.